Acoustic solution to characterize a mechanical construction steel induced microstructural changes - Vera Alvarado, Jorge Wilfredo; Caballero García, Luis Fernando; Taboada Neira, Martin (LACCEI, 2024)
To evaluate the useful life of a component in service, it is important to know the evolution of the mechanical properties; such characterization is not feasible using conventional methods because they are inherently destructive. Therefore, the objective of the research was to present a non-destructive technological alternative to determine the hardness of a medium-carbon mechanical construction steel through acoustic measurements obtained by ultrasound. Nine experimental runs were planned, for this purpose the heating temperature and cooling severity were varied to induce microstructural differences and therefore their properties. Each sample was characterized by optical microscopy, hardness measurements and acoustic properties by ultrasound. The results subjected to statistical tests reported that there is a significant difference in the measurement of its properties between one sample and another, the experimental data arranged in a contour graph showed that hardness presents a negative correlation with respect to the speed and attenuation measurements. The harder the material, the greater the resistance to the propagation of the ultrasonic beam due to the structural effect of the phases. The correlation obtained is presented as a new technological solution aimed at obtaining mechanical properties through acoustic measurements.